KINETICS AND ISOTHERMS OF LEAD (II) IONS ADSORPTION ONTO CHELATING SCHIFF BASE DERIVED FROM 2-HYDROXY-2-PHENYLACETOPHENONE AND 2-AMINOBENZOIC ACID - Muhammad, A. S.; Uduma, U. A.; Sani, S. (FUDMA Journal of Sciences, 2023)
The research is aimed at utilizing a Schiff base (SB) adsorbent derived from 2-aminbenzoic acid and Benzoin to study the kinetics and isotherms for adsorptive removal of lead (Pb2+) from simulated wastewater samples as well as evaluate the dependence of adsorbent’s adsorption capacity on select operational parameters (contact time and adsorbent dosage) using a batch adsorption technique. The SB was prepared by refluxing ethanolic solutions of Benzoin (0.01mol) and 2-aminbenzoic acid (0.01mol). The equilibrium adsorption data for lead (II) ions were fitted to Langmuir isotherm model. The maximum monolayer adsorption capacity of SB as obtained from Langmuir isotherm was 4.97 mg/g (R2 = 1.0000) for contact time and 4.93mg/g (R2 = 0.9999) at 0.5g for adsorbent dose. Kinetics data correlated well with the pseudosecond order kinetic model (R2 = 0.9999) more than with the pseudofirst order kinetic model (R2 = 0.9656). Characterization of the Schiff’s base by Fourier Transform Infrared Spectroscopy (FTIR) before and after adsorption of Pb2+ revealed that adsorption has taken place as evidenced by shifts and disappearances of important peaks in their spectra.
Keywords: Adsorption, Lead (II), Chelating, Schiff’s base, Acid